Swing on this : Australia's leading men of stage and screen with the 18-piece Swing on This big band. - Queensland Performing Arts Centre ([Brisbane?] : QPAC, 2017)
Poster featuring a photograph of Ben Mingay, Michael Falzon, Luke Kennedy and Rob Mills standing at the edge of a swimming pool. Title superimposed at the centre in pale yellow lettering. The QPAC and Queensland Government logos appear lower right.
Caption title.
"Swing on This is made up of musical theatre leading men, Michael Falzon, Luke Kennedy, Matt Lee, Rob Mills and Ben Mingay, singing a collection of classic swing songs reworked with a more contemporary style, as well as more recent popular music arranged for an 18 piece big band"--Wikipedia, viewed 2 June 2017, https://en.wikipedia.org/wiki/Swing_on_This
Keywords: Mingay, Ben -- Posters; Falzon, Michael -- Posters; Kennedy, Luke -- Posters; Mills, Rob -- Posters; Swing on This (Musical group) -- Posters; Singers -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian